Growth from two transient apical initials in the meristem of Selaginella kraussiana. - Harrison, C; Rezvani, M; Langdale, J (2007)
A major transition in land plant evolution was from growth in water to growth on land. This transition necessitated major morphological innovations that were accompanied by the development of three-dimensional apical growth. In extant land plants, shoot growth occurs from groups of cells at the apex known as meristems. In different land plant lineages, meristems function in different ways to produce distinct plant morphologies, yet our understanding of the developmental basis of meristem function is limited to the most recently diverged angiosperms. To redress this balance, we have examined meristem function in the lycophyte Selaginella kraussiana. Using a clonal analysis, we show that S. kraussiana shoots are derived from the activity of two short-lived apical initials that facilitate the formation of four axes of symmetry in the shoot. Leaves are initiated from just two epidermal cells, and the mediolateral leaf axis is the first to be established. This pattern of development differs from that seen in flowering plants. These differences are discussed in the context of the development and evolution of diverse land plant forms.